Wearable technology may assist in reducing jockeys' injuries if integrated into their safety vests: a qualitative study - Giusti Gestri, Lisa (Frontiers in Sports and Active Living, 2023)
While the term “safety vests” has been used to capture these products to reduce the potential for harm in jockeys under the Personal Protective Equipment (PPE) umbrella, much of the research in this area has focused on factors typically echoing health, well-being, physiological and cognitive function, and performance of horse riders with very little work about examining how its design may reduce the severity of jockeys' injuries. Due to the recent advances in technology and wearable sensors, the author considered a qualitative study focusing on the analysis of a real-life example involving end and co-dependent users in the design development of jockeys' safety vests. This little article offers an overview of the most popular jockeys' injuries, why there is a need for better protection, and also describes how data were collected and present a summary of the key findings to encourage future research in this field, aiming to create a new prototype. High-impact sports may potentially create severe injuries or deaths to athletes: thus, there is a strong faith in the application of wearable sensor data and data science to also enhance jockeys' safety vest performance.